Pengaruh Kemudahan dan Pengalaman Terhadap Minat Menggunakan Kembali Aplikasi PLN Mobile (Studi pada Pelanggan PLN ULP Malang Kota) - Lyra Ayu Sephia; Yulis Nurul Aini; Mohammad Maskan (INDO PUBLISHING, 2026)
The rapid development of digital services has encouraged people to adopt technology based applications that provide convenience and efficiency, including PLN Mobile as a digital electricity service platform. Nevertheless, the existence of various usage related problems suggests that ease of use and user experience are important factors that potentially influence customers intention to continue using the PLN Mobile application. The purpose of this research is to analyze the influence of ease of use and user experience on reuse intention of the PLN Mobile application. This research was a quantitative study that used a questionnaire as the data collection instrument, which was distributed to 103 respondents who were customers of PLN ULP Malang Kota and had used the PLN Mobile application at least once. The respondents were selected using a purposive sampling technique. The data were analyzed using multiple linear regression analysis and hypothesis testing. From the result of correlation analysis of ease of use and user experience on reuse intention, it was known that F count > F table (42,440 > 3,09), with a coefficient of determination was 0,448. This means there was influence of ease of use and user experience on reuse intention of 44,8% and the rest 55,2% was influenced by other factors not discussed in this research. Based on the result of the research, it can be concluded that ease of use and user experience significantly influence reuse intention. Therefore, the company is expected to maintain and improve the quality of its digital services by simplifying the use of the application and enhancing the user experience, so that customers’ intention to continue using the PLN Mobile application can increase sustainably